DEVELOPING BIOMATERIAL-BASED STRATEGIES TO ENHANCE THE DELIVERY AND ACCESSIBILITY OF BACTERIOPHAGE THERAPEUTICS - Bayat, Fereshteh (My University, 2023)
The primary goal of this research is to engineer solutions facilitating the utilization of bacteriophages as naturally occurring bactericidal agents for combatting multidrug-resistant (MDR) bacterial infections. Bacteriophages, which are bacterial viruses, represent self-replicating antibacterial agents known for their remarkable specificity in targeting bacterial cells. This specificity stands in sharp contrast to the indiscriminate and broad-spectrum actions of many currently employed antimicrobials across various sectors. Specificity of bacteriophages is a double-sided sword, often requiring large-scale phage hunting and phage biobank screening. This, combined with the lack of a global phage biobank can significantly limit access to phage therapeutics. I have developed a rapid, high-throughput platform focused on the detection of phage-mediated adenosine triphosphate (ATP) release via enzymatic ATP bioluminescence assay to identify highly lytic phages targeting MDR bacterial pathogens. I also used pullulan-trehalose sugar mixture to stabilize the ATP bioluminescence assay components at physiological temperatures. The sugar mixture also enhanced the desiccation tolerance of the ATP assay components along with phage, enabling the creation of all-inclusive shelf-stable tablets. The resulting tablets proved effectiveness and reliability in tracking phage-mediated bacterial cell lysis, and the pullulan-trehalose encapsulation significantly enhanced both the signal and desiccation tolerance of the phage and assay components. Next, I developed a bi-functional phage delivering nanoclay-based injectable hydrogel that can serve as both antibacterial and osteoinductive therapeutic hydrogel for treating bone and implant associated infections. The in vitro results for phage-loaded injectable hydrogels confirmed strong antimicrobial action against bacterial biofilms, in both biofilm prevention and biofilm dispersion challenges. Continuing the phage biomaterials research, I also co-developed a combination of phage-collagen conjugated liquid infused coating on titanium implant that enhanced osteointegration and was remarkably effective against implant-associated infections as a prophylactic measure in vivo. Lastly, and as a proof of the utility of phage biocontrol beyond biomedical applications, I demonstrated biofilm removal and full signal regeneration for dissolved oxygen (DO) sensors using a phage cocktail.
Keywords: Biomaterials, Phage delivery, Phage susceptibility